Health insurance generosity and conditional coverage: Evidence from medicaid managed care in Kentucky. (23rd March 2015) - Marton, James; Yelowitz, Aaron
<x xml:space="preserve">Abstract</x> This article estimates the impact of the introduction of Medicaid managed care (MMC) on the formal Medicaid participation of children. We employ a quasi‐experimental approach exploiting the location‐specific timing of MMC implementation in Kentucky. Using data from the March Current Population Survey from 1995 to 2003, our findings suggest that the introduction of MMC increases the likelihood of being uninsured and decreases formal Medicaid participation. This finding is consistent with an increase in "conditional coverage, " waiting until medical care is needed to sign up or re‐enroll in Medicaid. These effects are concentrated among low‐income children and absent for high‐income children. We find no evidence of "crowd‐in, " substituting private coverage for Medicaid. These results are robust to multiple placebo tests and imply the potential for less formal participation (i.e., more conditional coverage) among the Affordable Care Act‐Medicaid expansion population (which is likely to be primarily covered under MMC) than is typically predicted.